Visual communication, reproductive behavior, and home range of Hylodes dactylocinus (Anura, Leptodactylidae) - Narvaes, Patrícia; Rodrigues, Miguel Trefaut (Phyllomedusa: Journal of Herpetology, 2005)
We studied the signaling, reproductive and courtship behaviors of the diurnal stream-dwelling frog Hylodes dactylocinus. The repertoire of visual signals of H. dactylocinus includes foot-flagging, leg-stretching, body movements, and toe-wiggling. The visual signals are performed only by males and are used to defend territories against intruders and to attract females. Home range size varied from 0.12 to 13.12 m² for males (N = 44), and from 0.45 to 7.98 m² for females (N = 24); residency time varied from one to 12 months for males, and from two to 10 months for females. During the courtship of H. dactylocinus the male gives an encounter call towards an approaching female, touches her snout, and guides her to a previously dug nest. After oviposition, the female leaves the nest and returns to her own home range; the male remains calling after concealing the nest entrance.